Confirmatory Factor Analysis to Reduce the Knowledge and Economic Dimensions of the Behavior of Cerebral Palsy Parents - Khasanah, Al Um Aniswatun; Yuliana, Sri; Ikrom, Dhofirul Fadhil Dzil; Sholiha, Sangidatus; Dewi, Wardhani Utami (JTAM (Jurnal Teori dan Aplikasi Matematika), 2024)
This research is important to understand the behavior of parents of Cerebral Palsy (CP) children by reducing the complexity in understanding knowledge and economic dimensions, thus providing a structured approach to identifying factors that influence the psychology of children with CP. This study aimed to identify and reduce the dimensions that influence the behavior of parents of children with CFA.This study aimed to reduce the socio-economic dimensions and knowledge of the behavior of parents of Cerebral Palsy (CP) children using CFA. A quantitative approach with a cross-sectional design was used in this study to comprehensively examine the behavior of parents of children with CP. Purposive sampling was used to select 200 participants from various backgrounds. The instrument used was a 28-item questionnaire which was distributed online to collect data. The questionnaire has gone through rigorous testing, including CFA, determinant KMO test, Bartlett test PCA, and grouping of variables based on identified factors.Research methods , a quantitative approach with cross-sectional design, and purposive sampling were used to select 200 parents of children with CP from various backgrounds. The instrument in the form of a questionnaire with 28 statement items was distributed online. Data analysis was carried out using CFA, including the determinant test, Kaiser-Meyer-Olkin (KMO) test, Bartlett test, Principal Components Analysis (PCA), and grouping variables based on factors. Research in Lampung shows that the number of boys with CP is slightly higher, with the majority aged 1-5 years. Factor analysis identified three main dimensions: parental knowledge about CP, family economic situation, and parental behavior. Better knowledge and a stable economic situation are positively correlated with better parental behavior in caring for children with CP. Many parents experience high levels of stress due to the physical, emotional, and financial burden of caring for a child with CP. The research conclusion shows that the 28 statement items were successfully reduced to three main dimensions (knowledge, economics, and behavior) which have a significant relationship in the care of children with CP. These findings suggest the need for interventions to increase parental knowledge about CP and family economic stability to increase parental participation in child care.Findings the sex distribution of children with cerebral palsy in Lampung showed a slight excess in the number of boys, with the majority of children being in the age range of 1-5 years. Factor analysis identified three main dimensions: parental knowledge of CP, family economic situation, and parental behavior, where better knowledge and stable economic situation positively correlated with better parental behavior in caring for children with CP. Many parents experience high levels of stress in caring for a child with CP because of the physical, emotional, and financial burden that the condition brings. In conclusion, the 28 items of the statement are reduced to 3 dimensions or factors, including knowledge, economics, and behavior. Each dimension has a relationship with each other significantly to the behavior of parents of CP children.